A minimal monitoring approach for the treatment of hepatitis C virus infection (ACTG A5360 [MINMON]): a phase 4, open-label, single-arm trial. (April 2022) - Solomon, Sunil S; Wagner-Cardoso, Sandra; Smeaton, Laura; Sowah, Leonard A; Wimbish, Chanelle; Robbins, Gregory; Brates, Irena; Scello, Christine; Son, Annie; Avihingsanon, Anchalee; Linas, Benjamin; Anthony, Donald; et al.
Summary: Background: Despite widespread availability of direct-acting antivirals including generic formulations, limited progress has been made in the global adoption of hepatitis C virus (HCV) treatment. Barriers to treatment scale-up include availability and access to diagnostic and monitoring tests, health-care infrastructure, and requirement for frequent visits during treatment. Methods: ACTG A5360 was a phase 4, open-label, single-arm trial across 38 sites in Brazil, South Africa, Thailand, Uganda, and the USA. Key inclusion criteria were age of 18 years or older, evidence of active HCV infection (HCV RNA >1000 IU/mL) and HCV treatment-naive; patients with compensated cirrhosis and HIV/HCV co-infection were included but their enrolment was capped. All participants received a fixed dose combination of oral sofosbuvir (400 mg) and velpatasvir (100 mg) once daily for 12 weeks. The minimal monitoring (MINMON) approach consisted of four components: (1) there was no pre-treatment genotyping; (2) the entire treatment course (84 tablets) was dispensed at entry; (3) there were no scheduled visits or laboratory monitoring; and (4) there were two points of remote contact, at week 4 for adherence and week 22, to schedule outcome assessment at week 24 (−2 weeks to +4 weeks). Participants who missed the week 24 window could return for a visit to assess treatment response any time before week 72. Unplanned visits for any reason were permissible before the week 24 visit. The primary efficacy outcome was sustained virological response (SVR), defined as HCV RNA less than the lower limit of quantification measured at least 22 weeks post-treatment initiation; the primary safety outcome was serious adverse events. The primary efficacy analysis included all participants who initiated treatment, using a missing=failure approach. The primary safety analysis included all participants who initiated treatment and had at least one post-treatment assessment. This trial is registered at ClinicalTrials.gov, NCT03512210 . Findings: Between Oct 22, 2018, and July 19, 2019, 400 participants were enrolled across all 38 sites; 399 initiated treatment. At the SVR assessment visit, 355 (89%) of 397 participants reported taking 100% of the trial medication during the 12-week treatment period; two patients did not have any follow-up visits after the entry visit and were excluded from the safety analyses. Overall, 379 of the 399 who initiated treatment had an SVR (95·0%, 95% CI 92·4–96·7). 14 (4%) of 397 participants reported serious adverse events between treatment initiation and week 28; none were treatment related or led to treatment discontinuation or death. 15 (4%) of 399 participants had unplanned visits; none were related to treatment. Interpretation: In this diverse global population of people with HCV, the MINMON approach with sofosbuvir–velpatasvir treatment was safe and achieved SVR comparable to standard monitoring observed in real-world data. Coupled with innovative case finding strategies, this strategy could be crucial to the global HCV elimination agenda. Funding: US National Institutes of Health and Gilead Sciences.